An Analysis of Farmers' Preference for Bt Cotton with Reference to Dharampuri District - Sivakumar, R. K.; Ajjan, N.; Sivakumar, S. D. (Indian Journal of Marketing, 2005)
Cotton has been a premier agricultural crop of India playing a pivotal role in the national economy in both rural and urban sector. It contributed about 65 percent of the raw material for textile industry and also one-third of total foreign exchange earning of India amounting to nearly $ 11.00 billion. Cotton sustains huge employment in the rural and urban sector and plays a key role in economics and trade activities within the country. Being a cash crop, farmers were highly sensitive to pest incidence and resorted to indiscriminate and excessive application of recommended and non-recommended pesticides, which in turn led to the elimination of beneficial parasites and predators. Indiscriminate use of synthetic Pyrethroids led to whitefly resurgence in many parts of the country. In Southern State of Andhra Pradesh many cotton farmers committed suicide due to crop failure and losses.